Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Konsumen di Toko Vani Fashion di jalan Gohor Lama Kabupaten Langkat Kecamatan Wampu - Cornelia Ivani; Tri Kartika Yudha; Tika Indria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The research analysis aims to determine whether price influences consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Does product quality influence consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Do product price and quality influence consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. This study uses multiple linear regression. The sample research was conducted using the